The incidence of workplace pensions: Evidence from the UK's automatic enrollment mandate - Rachel Scarfe; Daniel Schaefer; Tomasz Sulka (Johannes Kepler University of Linz, Department of Economics, 2024)
We examine who bears the costs of mandated workplace pension programs, exploiting the quasi-experimental rollout of automatic enrollment in the UK. Total compensation (take-home pay plus employer contributions) increases, driven by employer contributions, while the amount of take-home pay decreases. These effects differ by employer size, with take-home pay declining to an extent in the largest firms that we can rule out a pass-through to employees of more than 47%, significantly less than in smaller firms. Our findings provide the first evidence that large employers shift the cost of mandated automatic enrollment onto employees.
Keywords: D21; H22; J32; J38; 330; Employer-sponsored retirement savings; Incentive design; Mandated benefits; Staggered difference-in-differences